Antecedents and Consequences of FOMO in Tourism: an Empirical Literature Review - Kurniawan, Cahya Nova; Susilo, Eko Agus (Profit: Jurnal Adminsitrasi Bisnis, 2024)
This research aims to systematically review the literature on the drivers and consequences of the fear of missing out (FOMO) phenomena in the tourism context. This study employed a systematic literature review following PRISMA reporting guidelines. The writers searched the online database Elsevier (Scopus) for scholarly publications published in English that can be accessed throughout the databases. This study does a systematic literature review using data from 56 articles. According to the findings, three elements of antecedents contribute to FOMO in the tourism context: electronic word of mouth, reference groups, and perceived loneliness. Then, three variables are the results of the FOMO: intention to seek information, intention to visit, and positive well-being. FOMO is a "fear of being left behind" phenomenon that occurs among online users as a result of the different activities available on social media. Tourism enterprises will likely be able to use the FOMO phenomenon as an advertising tool that will influence the emergence of motivation to visit and create new experiences for travelers. For travelers, the FOMO phenomenon is predicted to be a personal motivation, particularly in meeting the desire for self-esteem and avoiding undesirable attributes such as fear and loneliness.